2021
DOI: 10.1177/03635465211001095
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Bone Fusion With Arthroscopic Double-Button Latarjet Versus Open-Screw Latarjet

Abstract: Background: Recently, arthroscopic double-button Latarjet (AL) has provided an alternative to conventional open Latarjet (OL) in the treatment of anterior shoulder instability with glenoid bone loss. Therefore, theoretically, the faster fusion is obtained, the sooner return to sports under safe conditions can occur. The emerging flexible fixation of the bone block has clearly offered a new approach to achieve bone fusion. However, the period required to achieve this goal remains controversial. Purpose/Hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Therefore, the time required for bone fusion to allow return to sports under secure conditions is critical after a Latarjet procedure. Bonnevialle et al 8 found the rates of fusion were 41% and 100% for the screw fixation and suture button fixation groups at 3 months postoperatively, respectively. In our study, we found that the rate of bone healing with screw fixation was not significantly different at 3 months postoperatively (87.3% vs 83.3%).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, the time required for bone fusion to allow return to sports under secure conditions is critical after a Latarjet procedure. Bonnevialle et al 8 found the rates of fusion were 41% and 100% for the screw fixation and suture button fixation groups at 3 months postoperatively, respectively. In our study, we found that the rate of bone healing with screw fixation was not significantly different at 3 months postoperatively (87.3% vs 83.3%).…”
Section: Discussionmentioning
confidence: 97%
“…Internal rotation was determined as the highest spine level that the patient’s thumb could reach behind the back: above T7 (10 points), T7 to T12 (8 points), T12 to L3 (6 points), L3 to sacrum (4 points); sacrum to greater trochanter (2 points); and below the greater trochanter (0 points), as performed for the Constant score. 8 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, some studies have found comparable load to failure 31 and functional results 28 to screw fixation without complications related to hardware removal, 6 , 9 , 16 , 28 while others have indicated delayed graft fusion with greater graft mobilization. 2 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…5 Although several studies have shown the advantages of using suture button fixation in the Bristow-Latarjet or Eden-Hybinette procedure, [13][14][15] the potential inferior biomechanical strength of suture button fixation is still in concern. 16,17 This Technical Note introduced an arthroscopic "doubleinlay" Eden-Hybinette procedure with modified suture button fixation for the revision of failed Bristow-Latarjet. This technique has two "Mortise-Tenon" structures.…”
Section: Introductionmentioning
confidence: 99%